2008
DOI: 10.1021/es8004514
|View full text |Cite
|
Sign up to set email alerts
|

Screening Chemicals for the Potential to be Persistent Organic Pollutants: A Case Study of Arctic Contaminants

Abstract: A large and ever-increasing number of chemicals are used in commerce, and researchers and regulators have struggled to ascertain that these chemicals do not threaten human health or cause environmental or ecological damage. The presence of persistent organic pollutants (POPs) in remote environments such as the Arctic is of special concern and has international regulatory implications. Responding to the need for a way to identify chemicals of high concern, a methodology has been developed which compares experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 18 publications
3
126
0
Order By: Relevance
“…A previous work reported that a group of haloderived triazine chemicals is among the list of potential POPs that could be present in the Arctic (10). Thus, it is important to monitor this group of HFRs in the environment to properly assess the potential exposure effects on ecosystems and humans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous work reported that a group of haloderived triazine chemicals is among the list of potential POPs that could be present in the Arctic (10). Thus, it is important to monitor this group of HFRs in the environment to properly assess the potential exposure effects on ecosystems and humans.…”
Section: Resultsmentioning
confidence: 99%
“…However, these alternative products might also have similar semivolatile properties, and their environment behaviors and underlying toxic effects are still unclear. Several of them have been identified as emerging chemicals that are present in the environment, such as 1,2,5,6,9,10-hexabromocyclododecane (HBCD), Dechlorane Plus and several others have been detected in different environmental matrices (1,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) and biological samples (18).…”
Section: Introductionmentioning
confidence: 99%
“…Brown and Wania [44] use a minimum hydroxyl radical atmospheric oxidation half-life of two days as the criterion for long-range air transportation. According to their atmospheric half-life times, chlorinated OPs are not sufficiently persistent in the atmosphere to be classified as POP substances, but their calculated photooxidation half-lives in air are nevertheless sufficient for short-range or medium-range atmospheric transportation.…”
Section: Atmospheric Transport and Photodegradationmentioning
confidence: 99%
“…al ., 1992;Schreitmuller and Ballschmiter, 1995;Lakaschus et al, 2002;Jantunen et al, 2004;Shen et al, 2004;Ding et al, 2007;Brown and Wania, 2008;Lohmann et al, 2009;Breivik et al, 1999). Briefly, HCHs have been used mainly in the Northern Hemisphere from 1940s to 2000 with technical mixtures containing 55-80 % α-HCH, 5-14 % β-HCH and 8-15 % γ -HCH (Iwata et al, 1993;Lakaschus et al, 2002).…”
Section: Introductionmentioning
confidence: 99%